A comparative evaluation of two investigational meningococcal ABCWY vaccine formulations: Results of a phase 2 randomized, controlled trial. Issue 21 (15th May 2015) - Block, Stan L.; Szenborn, Leszek; Daly, Wendy; Jackowska, Teresa; D'Agostino, Diego; Han, Linda; Dull, Peter M.; Smolenov, Igor
Highlights MenABCWY vaccines were immunogenic against serogroups ACWY and serogroup B test strains. MenABCWY vaccines were immunologically noninferior to MenACWY-CRM. Reactogenicity profiles of MenABCWY vaccines were similar to 4CMenB with no safety concerns identified.